Улогата на владините политики во промоција и поттикнување на инвестициите во глобалната економија - Палашевски, Јовица (Економски факултет, УКИМ, Скопје, 2016)
The doctoral dissertation is structured in four parts that complement each other creating a picture of the aspects of globalization and foreign direct investment and their impact on economic development, analyzing the conditions, characteristics and trends globally and in the country. The main hypothesis of the paper is to see the role of government policies in attracting foreign direct investment in the global economy, with special reference to Macedonia. The focus of the research e consideration aspects of globalization in terms of investment, that is organized and reorganized economic activities across dynamic networks of relationships between TNCs country, FDI and international agreements. In the paper, particular attention is paid to the processes related to attracting foreign direct investment in the country. Despite macroeconomic policy and foreign investment we have analyzed the parameters and factors that determine the attractiveness of the Republic of Macedonia for foreign investors according to the study by the World Bank - Doing Business, as compared to the countries of the SEE region. Presents the instruments and institutions, as well as their placement in terms of attracting FDI in the country. Analyzed are part of the tools that can serve the country to promote their business interests, such as economic diplomacy, Diaspora and territorial marketing. At the end is provided empirical research conducted through a questionnaire which explores the situations related government policies in the process of attracting foreign direct investments in the country.
Докторска дисертација одбранета во 2016 година на Економскиот факултет во Скопје, под менторство на проф. д–р Наталија Николовска.
Keywords: globalization, foreign direct investment, government policies, economic diplomacy